The role of mitophagy in female reproductive system diseases: from molecular mechanisms to therapeutic strategies - Zhao, Huiyi; Wang, Ying; Han, Han; Jiang, Yue; Ji, Xiang; Zhang, Yuehui (Frontiers in Endocrinology, 2025)
Mitophagy is a catabolic mechanism that selectively degrades damaged mitochondria and precisely modulates mitochondrial content, thereby maintaining intracellular homeostasis under stress conditions. To date, most reviews on mitophagy have predominantly focused on neurodegenerative diseases, cardiovascular disorders, cancer, metabolic syndromes, and inflammation- or immune-related diseases. In recent years, accumulating evidence has highlighted the critical involvement of mitophagy in various physiological and pathological processes associated with female reproduction. This review systematically synthesizes existing evidence to elucidate the regulatory roles of mitophagy during the occurrence and development of follicles, oocyte fertilization, and embryo implantation, as well as its essential contributions to the pathogenesis of endometriosis, polycystic ovary syndrome, primary ovarian insufficiency, and ovarian aging. Furthermore, we outline current therapeutic strategies targeting mitophagy while emphasizing the potential value of traditional Chinese medicine. Our aim is to provide novel insights into the regulatory network and specific targets of mitophagy in female reproduction, facilitate clinical translation, and offer innovative approaches for managing female reproductive health.